2015
DOI: 10.1002/eco.1651
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of chromophoric dissolved organic matter in a large floodplain river: control factors and relations with phytoplankton during a low water period

Abstract: Chromophoric dissolved organic matter (CDOM) affects ecological processes in freshwater environments. Few studies assessed its spatial variability and relations with phytoplankton in floodplain rivers. Therefore, these topics were examined in a hydrological connectivity gradient in the Middle Paraná system. Absorption coefficients at 250 and 365 nm were measured to estimate CDOM concentration and molecular weight (MW), to find their explanatory limnological variables (Redundancy Analysis, RDA), and to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This is quite different from most reports on phytoplankton composition in large tropical rivers, particularly of South America (e.g. Garcia de Emiliani, ; Lewis et al ., ; Davies et al ., ; Devercelli et al ., ; O'Farrell & Izaguirre, ) but also from Africa (Prowse & Talling, ; Talling & Rzόska, ): one would have expected dominance of diatoms during both discharge conditions, owing to light limitation resulting from the TSM concentration in the mainstem and large tributaries, and from high DOC in the blackwater tributaries (Mayora, Devercelli & Frau, ). Indeed, considering a mean daily surface irradiance of 750 μE m −2 s −1 , calculated from continuous recordings during the cruises, the mean light exposure of phytoplankton would have been on average 35 μE m −2 s −1 in FW versus 71 μE m −2 s −1 in HW (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…This is quite different from most reports on phytoplankton composition in large tropical rivers, particularly of South America (e.g. Garcia de Emiliani, ; Lewis et al ., ; Davies et al ., ; Devercelli et al ., ; O'Farrell & Izaguirre, ) but also from Africa (Prowse & Talling, ; Talling & Rzόska, ): one would have expected dominance of diatoms during both discharge conditions, owing to light limitation resulting from the TSM concentration in the mainstem and large tributaries, and from high DOC in the blackwater tributaries (Mayora, Devercelli & Frau, ). Indeed, considering a mean daily surface irradiance of 750 μE m −2 s −1 , calculated from continuous recordings during the cruises, the mean light exposure of phytoplankton would have been on average 35 μE m −2 s −1 in FW versus 71 μE m −2 s −1 in HW (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken bimonthly in six occasions (January 2013-March 2014), including littoral and open water sites (n = 12). The Miní Lake is located within the Paraná River floodplain, it is permanently connected to the river with a residence time between 1 and 10 days, and modulated by hydrological and sedimentological pulses of the fluvial system (Mayora et al 2013(Mayora et al , 2016. In Miní Lake, samplings were carried out approximately fortnightly from November 2009 to December 2010, and from January to December 2012 (n = 38).…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
“…High flushing rates in Miní Lake hinder C. furcoides local growth and precludes it from negatively affect the local community. Further, a high degree of native species connectivity constitutes a mechanism that diminishes the negative effects of invasion (Howeth 2017) and increase total phytoplankton richness (Devercelli et al 2014, Mayora et al 2016. The analysis of invasion processes explicitly including network effects should be conducted to determine the relative contribution of dispersal versus local effects.…”
Section: Invasion Outcome: Coexistence or Negative Effectsmentioning
confidence: 99%
“…Previous studies have shown a decrease in suspended particulate matter and an increase in CDOM and phytoplankton biomass from the main channel (MC) towards the most isolated floodplain water bodies (Mayora, Devercelli, & Frau, ; Unrein, ; Zalocar de Domitrovic, Devercelli, & García de Emiliani, ). The spatial differences are more evident during isolation periods due to the effects of local driving forces (Maine, Suñe, & Bonetto, ; Roberto, Santana, & Thomaz, ; Thomaz, Bini, & Bozelli, ).…”
Section: Introductionmentioning
confidence: 99%